Revitalisasi Keterampilan Kreatif Pesisir: Pengembangan Industri Kerajinan Nipah di PKBM Mina Center Langkat: Pengabdian - Kartini Harahap; Onan Marakali Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This Economic and Social Service Program aims to Revitalize Coastal Creative Skills in Langkat Regency through the Development of a Nipah Craft Industry Based on Non-Formal Education at the Mina Center Community Learning Center (PKBM Mina Center). Coastal communities in Langkat Regency have great potential in processing nipah palms into creative craft products, but face various challenges, such as limited processing skills, limited marketing access, minimal financial literacy, and low environmental awareness. In addition, the capacity of the partner (PKBM Mina Center) to provide technical and marketing support is also not optimal. This program offers solutions through intensive training and mentoring to coastal communities and partners, with a focus on improving nipah palm processing skills into high-value creative craft products, introducing digital marketing through social media and e-commerce, financial literacy and business management training, introducing simple technology to increase production efficiency, and environmental education on the importance of preserving nipah palms and coastal ecosystems. This program consists of three main stages: preparation, implementation, and evaluation. The preparation stage includes identifying needs, developing training materials, and coordinating with stakeholders. The implementation stage includes skills training, technical mentoring, digital marketing training, business management education, and environmental education. The evaluation phase is conducted to monitor and evaluate the program's success and provide feedback for improvement. This program is expected to increase the competitiveness and sustainability of the nipah handicraft industry in Langkat Regency, while simultaneously encouraging inclusive local economic growth. Furthermore, the program also contributes to the achievement of higher education's Key Performance Indicators (KPI), such as student experiences outside campus, lecturers' off-campus